Proposal of indicators to measure university linkage: Perspectives of officials in public higher education institutions - Torres Salazar, Maria del Carmen; Escalante Ferrer, Ana Esther; García Domínguez, Norma Alicia (Education Policy Analysis Archives, 2020)
University linking is an activity that establishes alliances with various sectors within society. In this study, the links with the productive sector are analyzed. The objective of the text, based on the proposals of Spanish American authors, is to generate a linkage measurement model, made up of a set of easily understandable and measurable indicators, at first, for all academic units that make up the Autonomous University of Estado de Morelos (UAEM), Mexico. This is constituted as a case study to be available for other related institutions. The model was built with the focus group technique, and carried out with those responsible for linking the faculties, higher education schools, research centers and institutes of the UAEM with another organizations, and a review of the literature. The result of this work reports 13 indicators applicable to all academic units of the university in question, since they worked with representatives from all areas of knowledge. Each of the indicators proposes a method of calculation, which is intended to avoid the subjectivity of the ideas of some the authors reviewed and move from the conversion of social science proposals to more consistent data.